PERILAKU HIDUP BERSIH DAN SEHAT TATANAN TEMPAT - TEMPAT UMUM (Studi Kasus Pedagang Makanan Minuman di Terminal Purabaya Surabaya Tahun 2014) - Junanda Eka Prisandoyo; Ngadino .; Didik Sugeng Purwanto (Poltekkes Kemenkes Surabaya, 2014)
The so called Public Places are places where many people gather and perform activitiesinCidentally or continuously. Activities in public places are vulnerable to threats of disease transmission,either directly or indirectly. To maintain and improve health conditions, the PHBSway of life needs to bepractised. The purpose of the study was to determine the practice of the PHBSprinciples in public placesespecially among the food stalls.Basedon the method of data analysis this was considered a descriptive study with cross sectionalapproach. Data was gathered through questionnaires, check lists and observations. The number ofsamples in this study was 55 owners of food vendors. The data obtained were subjected to subsequentdescriptive analysis.Results of the study with regard to knowledge level showed that 63,6% of respondents havesufficient level of knowledge. attitudes the study showed that 63,6% of respondents were consideredadequate. While in terms of the action the study showed that 83,6% of respondents can in the IIIrdclaSSification, where among the 10 indicators there are only 7-9 qualified indicators that met therequirements, due to the absence of good garbage bins and lack of hand washing facilities.The study suggested that promotional programs need to be intensified to improve the PHBSparctices in public places. Managers of the bus terminal need to provide food vendors with proper handwashing facilities